Dispersion of helical axes during shoulder movements in young and elderly subjects - Temporiti, Federico; Furone, Roberta; Cescon, Corrado; Barbero, Marco; Gatti, Roberto (Journal of biomechanics, 2019)
The shoulder complex (SC) consists of joints with little congruence and its active and passive structures ensure its stability. Stability of the SC rotation centre during upper arm movements can be estimated through the analysis of Helical Axes (HAs) dispersion. The aim of this study was to describe shoulder HAs dispersion during upper limb movements performed with dominant and non-dominant arms by young and elderly subjects. Forty subjects participated in the study (20 young: age 24.8 ± 2.8 years and 20 elderly: age 71.7 ± 6.3 years). Subjects were asked to perform four cycles of 15 rotations, flexions, elevations and abductions with one arm at a time at constant speed. Reflective markers were placed on participants’ arms and trunk in order to detect movements and the HAs dispersion with an optoelectronic system. Mean Distance (MD) from the HAs barycenter and Mean Angle (MA) were used as HAs dispersion indexes. Young subjects showed significant lower MD compared to the elderly during all motion ranges of rotation, flexion and elevation (p < 0.001). Moreover, the MD was lower in the dominant arm compared to the contralateral for rotation (p = 0.049) and flexion (p = 0.019). The results may be due to joint degeneration described in elderly subjects and differences in neuromuscular control of SC stability.